Avaliação de células mielóides supressoras e linfócitos T em indivíduos longevos - Alves, Amanda Soares [UNIFESP] (2018)
Modern society has been facing a major demographic revolution that is the population aging. The increase in life expectancy depends on the adjusted function of several organs and tissues in order to deal with damaging events in life time. Successful aging seems to be dependent at least in part on the adequate function of the immune system. It has been reported that aging is associated with changes in the percentage of myeloid-derived suppressor cells (MDSC) and T lymphocytes besides the impairment of T cells functions. Our aim was to evaluate young and long-living individuals according to myeloid-derived suppressor cells; T cells proliferative response, phenotype, and cytokines secretion after mitogen stimulation. Non-institutionalized both gender long-living individuals (80 years old and over; 80+) from SABE study were evaluated and compared to young students from UNIFESP (20-30 years old). Aging was associated with reduced circulating number of leukocytes in older individuals (80+). The percentage of MDSC was higher in 80+ group whereas the absolute number of these cells was not statistically different when young and 80+ individuals were compared. Aged individuals also presented higher CD4/CD8 ratio, decrease of naïve and increase of EMRA cells mainly in CD8+ compartment. Under PHA stimulus 80+ individuals presented lower proliferative capacity, and decreased expression of IL-1, IL-2, IL-6, IFN-y, and TNF-alpha. Aging is a complex, multifactorial, and heterogeneous process and based on our results it is suggested that MDSC (percentage and absolute cell number), percentage of naïve and EMRA TCD8+ cells, CD4/CD8 ratio, proliferative T cell percentage, and cytokine levels could be used as biomarkers in aging individuals to predict pathologies, to indicate interventions and to evaluate interventions' efficacy. In addition, aging population presented very heterogeneous results, reinforcing the importance of an individualized treatment for these individuals.